The effect of body image and physical activity on depressive symptoms : a study on Icelandic adolescent girls and boys - Lovísa Dagmar Guðfinnsdóttir 1993- (2016)
The main focus of this research is depression among adolescents, what effect body image and physical activity may have on depression and gender different. Data from Icelandic Centre for Social Research and Analysis (ICSRA), Youth in Iceland 2014, was used for this current study. Participants were a random sample of 2055 Icelandic grammar school students in 8th, 9th and 10th grade. Factorial Analysis of Variance (FANOVA) was used to test for main and interaction effects. The results of this current study indicated that negative body image increases the likelihood of depression and physical activity decreases the likelihood of depression. Negative body image has stronger effect on depression among girls than boys, while the effect of physical activity on depression is not different between boys and girls. Results also indicated that physical activity does not buffer the effects between body image and depression. Keywords: body image, physical activity, depressive symptoms Markmið þessarar rannsóknar er að skoða þunglyndi hjá unglingum, hvaða áhrif líkamsímynd og hreyfing hefur á þunglyndi og hvort áhrifin séu mismunandi eftir kyni. Í þessari rannsókn voru gögn frá Rannsókn og Greiningu notuð, þar sem 2055 íslenskir grunnskóla nemendur í 8., 9. og 10. bekk svöruðu spurningalista. Með fjölbreytu-dreifigreiningu (FANOVA) voru könnuð meginhrif og samvirkni líkamsímyndar og hreyfingar á þunglyndi. Niðurstöður rannsóknarinnar gáfu til kynna að neikvæð líkamsímynd auki líkurnar á þunglyndi og að hreyfing dragi úr líkunum á þunglyndi. Neikvæð líkamsímynd hefur meiri áhrif á þunglyndi hjá stelpum en strákum, á meðan enginn munur er á kynjum varðandi áhrif hreyfingar á þunglyndi. Einnig gáfu þær til kynna að hreyfing dragi ekki úr áhrifum neikvæðrar líkamsímyndar á þunglyndi. Lykilhugtök: líkamsímynd, hreyfing, þunglyndi